Unfolding and characterizing the barriers and facilitators of scaling-up evidence-based interventions from the stakeholders' perspective: a concept mapping approach. Issue 2 (22nd June 2022) - Zhang, Xiaoyan; Zhao, Junqiang; Li, XueJing; Yan, Lijiao; Hao, Yufang; Liu, Jianping
ABSTRACT: Introduction and aims: Much attention has been paid to scaling-up evidence-based interventions (EBIs) in previous implementation science studies. However, there is limited research on how stakeholders perceive factors of the scaling-up of EBIs. This study aimed to identify the barriers and facilitators of scaling-up the nurse-led evidence-based practice of post-stroke dysphagia identification and management (EBP-PSDIM) from the stakeholders' perspective, and to assess their importance and feasibility. Methods: This study was conducted using concept mapping. Through purposive sampling, 18 stakeholders were recruited for brainstorming in which they responded to the focus prompt. Here, statements regarding perceived barriers and facilitators to EBI scaling-up were elicited and then sorted by similarity before being rated based on the importance and feasibility. Cluster analysis, multidimensional scaling, and descriptive statistics were utilized to analyze the data. Results: Ultimately, 61 statements perceived to influence the scaling-up were grouped into four primary clusters, that is, community-related factors, resource team-related factors, evidence-based practice program-related factors, and scaling-up strategy-related factors. The 'perceived needs of the community' was rated as the most important and feasible factor to address, whereas 'costs/resource mobilization' was rated as the least important and feasible one. Conclusion: From the stakeholders' perspective, factors involved in the EBP-PSDIM program scaling-up were initially validated as being multidimensional and conceptually distinct;The importance and feasibility ratings of the barriers and facilitators could be used to help decision-makers to prioritize the most appropriate factors to be considered when developing implementation strategies.